Foreign Workers’ Smooth Repatriation and Reassessment of Crucial Factors: A Mixed-Method Study of Migrant Labourers in Malaysia - Al Masud, Sheikh Mohammad Maniruzzaman; Rohana, Hamzah; Hasan, Ahmad (Institute of Research and Journal, 2022)
Malaysia has witnessed an influx of foreign workers, mainly due to its rapidly expanding economy. However, Malaysian labour migration policies have remained a short-term solution to fill instant labour shortages since the relevant authority introduced it. The current policy has weaknesses due to not successfully controlling foreign workers at all phases, including therepatriation stage. Consequently, low-skilled or irregular migrant workers prevail in the labour market,and their number is increasing,which is discussed frequently.This study aimed to identify crucial factors related to foreign workers requiring reconsideration at the repatriation phase. It was a sequential exploratory mixed-method study. Data were collected using qualitative (in-depth interviews)0190 and quantitative (face-to-face surveys) methods. The study found that for impeccable return of foreign workers (FWs), some repatriation factors should be reassessed, such as providing various training programs and information about further employment, introducing the online job-matching platform, sharing success stories of reintegration, giving career certificates, confirming departure guarantee insurance, extending work permits and approving PR (permanent residency) status for expert workers. The findings of this study will help in redesigning foreign worker repatriation policies. Moreover, the results will also assistin reducing illegal/irregular foreign workers inside Malaysia andensurea smooth return of foreign workers to their country of origin after completing the employment contract. Keywords - Low-Skilled Foreign Workers; Repatriation Phase; Providing Training Programs, Giving Information About Employment, Online Job-Matching Platform, Sharing Successful Stories, Providing Career Certificate, Departure Guarantee Insurance, Extending Work Permit, Approving Pr Status.